Evaluation of some arylhydrazones of p-aminobenzoic acid hydrazide as antimicrobial agents and their in vitro hepatic microsomal metabolism - (:unkn) unknown (My University, 1995)
Benzoic acid p-amino-[(substitutedphenyl/pyridylmethylene] hydrazide derivatives were synthesised by interaction of p-aminobenzoic acid hydrazide with various aromatic aldehydes. The structures of the compounds were elucidated by use of their UV, IR, 1H-NMR and mass spectral data. These compounds were also evaluated for antimicrobial activity. The in vitro hepatic microsomal metabolism of benzoic acid p-amino-[(4-fluorophenyl)methylene]hydrazide (2d), a selected prototype from these compounds was also carried out.
Keywords: antimicrobial activity; hydrazones; in vitro metabolism